Does participation in therapeutic exercise programs after finishing oncology treatment still ensure an adequate health status for long‑term breast cancer survivors? A ≥ 5 years follow‑up study. - Álvarez‑Salvago, Francisco; Jiménez-García, José Daniel; Martínez-Amat, Antonio; Pujol-Fuentes, Clara; Atienzar-Aroca, Sandra; Molina-García, Cristina; Aibar-Almazán, Agustín (Springer, 2023)
Purpose: The aims of this study were to evaluate whether the effects of two therapeutic exercise programs are sustained over time (≥ 5 years) in long-term breast cancer survivors (LTBCS). Second, to determine the influence of the current level of physical activity (PA) performed on cancer-related fatigue (CRF) that these patients may present ≥5 years later. Methods: A prospective observational study was conducted with a cohort of 80 LTBCS in Granada during 2018. Firstly, considering their participation in one of the programs, they were allocated into two groups: usual care and therapeutic exercise program, to assess CRF, pain and pressure pain sensitivity, muscle strength, functional capacity, and quality of life. Secondly, they were also classified into 3 groups according to current level of weekly PA performed: ≤ 3, 3.1-7.4, and ≥ 7.5 (MET-hour/week) respectively, to assess its impact over CRF. Results: Although the positive effects of the programs are not sustained over time, a trend toward significance can be observed for a greater reduction in overall CRF levels, lower intensity of pain in the affected arm and cervical region, and greater functional capacity and quality of life in the group that underwent therapeutic exercise. Additionally, 66.25% of LTBCS are inactive ≥ 5 years after completion of the program and furthermore, such inactivity is accompanied by higher CRF levels (P .013 to .046). Conclusion: The positive effects of therapeutic exercise programs are not maintained over time for LTBCS. Additionally, more than half of these women (66.25%) are inactive ≥ 5 years after completion of the program, this inactivity being accompanied by higher levels of CRF.
https://openpolicyfinder.jisc.ac.uk/id/publication/8241?from=single_hit
Keywords: Cáncer de mama - Complicaciones y secuelas; Enfermos de cáncer - Rehabilitación; Ejercicio físico; Fatiga (Fisiología); Calidad de vida; Long-term survivorship; Breast cancer; Fatigue; Quality of life; Physical activity; Rehabilitation